Aberrant functional connectivity between the suprachiasmatic nucleus and the superior temporal gyrus: Bridging RORA gene polymorphism with diurnal mood variation in major depressive disorder - Chen, Zhilu; Tao, Shiwan; Zhu, Rongxin; Tian, Shui; Sun, Yurong; Wang, Huan; Yan, Rui; Shao, Junneng; Zhang, Yujie; Zhang, Jie; Yao, Zhijian; Lu, Qing (Journal of psychiatric research, 2021)
Diurnal mood variation (DMV), a common symptom of major depressive disorder (MDD), is associated with circadian related genes and dysregulation of the suprachiasmatic nucleus (SCN). Previous research confirmed that the RORA gene is involved in the regulation of circadian rhythms. In this study, we hypothesized that polymorphisms of RORA may affect DMV symptoms of MDD through functional changes in the SCN. A total of 208 patients diagnosed with depression and 120 control subjects were enrolled and underwent a resting-state functional magnetic resonance imaging (rs-fMRI). Blood samples were collected and genotyping of 9 RORA gene SNPs were performed using next-generation sequencing technology. Patients were categorized as an AA genotype or C allele carriers based on RORA rs72752802 polymorphism. SCN-seed functional connectivity (FC) was compared between the two groups and correlation with severity of DMV was analyzed. Finally, a mediation analysis was performed to further determine FC intermediary effects. We observed that rs72752802 was significantly associated with patients’ DMV symptoms. C allele carriers of rs72752802 showed significantly decreased FC between the right SCN and right superior temporal gyrus (rSTG). This was also correlated with DMV symptoms. In addition, the rs72752802 SNP influenced DMV symptoms through intermediary effects of SCN-rSTG connectivity. The study presented here provides a neurological and genetic basis for understanding depressed patients experiencing DMV. •RORA rs72752802 polymorphism showed a significant association with DMV in depression where C allele was risk allele.•The FC of the suprachiasmatic nucleus significant decreased in risk allele carries compared to non-carriers.•Abnormal FC in the SCN took part in mediating the effects of rs72752802 polymorphism and DMV symptom in depression.